СТРУКТУРУВАННЯ ЗМІСТ ОСВІТИ ЯК УМОВИ ВДОСКОНАЛЕННЯ ПІДГОТОВКИ МАЙБУТНЬОГО ВИКЛАДАЧА У ВИЩІЙ ШКОЛІ (Педагогіка вищої та середньої школи, 2022)
The structuring of the contents of education is oriented on the unity, coordination and presentation of educational information. It helps to organize the process of education on higher-level quality. The technology of structuring of contents of education includes: of definition of the contentional, operational, practical, supplementary, enlarging and control elements of education. The structuring gives the possibility to work out the model programmed of educational course on the basis of which every student can work out individual programmer of educational activity. It enables the student to work according to his intentions ad possibilities, to study on the basic level, to provide self-development and training of the future specialist.